Extending McKinsey's 7S model to understand strategic alignment in academic libraries. Issue 5 (10th June 2019) - Cox, Andrew Martin; Pinfield, Stephen; Rutter, Sophie
Abstract : Purpose: The purpose of this paper is to conceptualise the issues of alignment for changing academic libraries by using and extending McKinsey's 7S model. Design/methodology/approach: Theoretical work was conducted to consider and extend the 7S model for the situation of academic libraries. Empirical data were then used to confirm the value of these extensions and suggest further changes. The data to support the analysis were drawn from 33 interviews with librarians, library and non-library academics and experts, and a survey of UK library staff. Findings: In the academic library context, the 7S model can be usefully extended to include three library functions (stuff, space and services) and users. It can also include institutional influences and stakeholders, and aspects of the external environment or situation, including suppliers and allies. The revised model then provides a useful framework within which data about library change can be analysed. Perceived barriers to successful performance fit the model and enable the identification of seven challenges of alignment. Research limitations/implications: The resulting model has potential applications such as in the structuring analysis of academic library performance, mapping future directions of development and for exploring variations across the sector and internationally. Practical implications: The revised model can be used by practitioners to think through their own strategic position and to act to shape their future, in the light of seven major areas of alignment. Originality/value: The paper extends a well-known model used in strategy, to produce a more comprehensive, sector-specific analytic tool.